MBSAP application to UAV-based wildfire detection and communication - Crawford, Setrige W., author; Eftekhari Shahroudi, Kamran, advisor; Borky, Mike, committee member; Kreidenweis-Dandy, Sonia, committee member; Bradley, Thomas, committee member; Herber, Daniel, committee member (Colorado State University. Libraries, 2023)
By applying the concepts of the Model Based Systems Architecture Process [90] we were able to link stakeholder needs and operational scenarios (Use Cases) to the preliminary design validation of an autonomous hybrid electric/ gas turbine UAV (H-UAV) intended for wildfire detection and communication. The salient stakeholder requirements were captured, operational scenarios identified, trade study was completed, competing architectures were interlinked to a design exploration (DSE) and preliminary airframe sizing, where a user could probe the bounds of design variables in a probabilistic manner to reveal all necessary sensitives and confirm system behaviors were consistent with stakeholder requirements (spiral verification and validation). This thesis takes the reader through this method and the development of each viewpoint, using Cameo Systems Modeler, starting with the Operational Viewpoint, then refinement to the Logical viewpoint and finally development of the Physical Viewpoint. Emphasized, is the use of a coupled architecture model (digital twin – virtual prototype) to confirm system behaviors against requirements and to graphically display system sensitivities. The deeper details of the DSE method and the trade study were previously published [119]. This paper focuses more on the MBSAP approach, the MBSE artifacts and reflects on the benefits of an interlinked model.[7] The method developed affords the researcher a set of tools to efficiently converge on an affordable system solution which meets stakeholder needs and operational requirements for a locally owned and operated wildfire detection and communication system. Further, the MBSAP method is systems agnostic in that. the approach, yields equally effective results whether applied to more software intensive systems, or more mechanical aerospace system (H-UAV) instantiations.
Keywords: MBSAP; system engineering; wildfire; MBSE; hybrid propulsion; UAV